2009
DOI: 10.1108/09513570910945651
|View full text |Cite
|
Sign up to set email alerts
|

The preservation of indigenous accounting systems in a subaltern community

Abstract: Purpose -The paper examines how indigenous accounting practices are mobilised in the daily life of a subaltern community, and how and why the members of that community have managed to preserve such practices over time despite external pressures for change.Methodology/approach -An ethno-methodological field study is employed to produce a text informing the ways in which people engage in social accounting practices. It uses the concepts of 'structuration theory' to understand how indigenous accounting systems ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 52 publications
0
52
0
5
Order By: Relevance
“…We would also advise them to play a more supportive role in stimulating development by making room for di-38 versity based on differences in historical and political contexts. Localized and indigenous accounting technologies should perhaps be encouraged rather than discarded (see Jayasinghe & Thomas, 2009;Jayasinghe & Wickramasinghe, 2011). They may, in fact, be preferred to a bombardment of Westerncentric accounting tools (see also Abdul-Rahaman et al, 1997;Allen, 2009, pp.16-24;De Renzio, 2006).…”
Section: What Do We Need To Know? Reflections and Directions For Futumentioning
confidence: 99%
“…We would also advise them to play a more supportive role in stimulating development by making room for di-38 versity based on differences in historical and political contexts. Localized and indigenous accounting technologies should perhaps be encouraged rather than discarded (see Jayasinghe & Thomas, 2009;Jayasinghe & Wickramasinghe, 2011). They may, in fact, be preferred to a bombardment of Westerncentric accounting tools (see also Abdul-Rahaman et al, 1997;Allen, 2009, pp.16-24;De Renzio, 2006).…”
Section: What Do We Need To Know? Reflections and Directions For Futumentioning
confidence: 99%
“…the extent to which individual papers explicitly build on and synthesize the previous literature, we see that very few papers (13%) cite 10 or more previous works (e.g. Englund & Gerdin, 2008;Jack & Kholeif, 2008;Jayasinghe & Thomas, 2009). The table also shows that more than half of the papers published from 2001 and onwards cite five or less previous works.…”
Section: B Communication Structure Within the Ma Literaturementioning
confidence: 99%
“…A dominating part of this literature has shown that subordinates may side-step various 'management-initiated' attempts for MA change, through access to resources such as technical/local knowledge , physical distance from superiors (Ouibrahim & Scapens, 1989), absence of clearly defined measurement systems , or complex command structures . However, the literature has also provided insights into how dominating groups may preserve a certain form of MA, through drawing upon their social positions and asset ownership (Jayasinghe & Thomas, 2009).…”
Section: E Sources Of Continuity and Changementioning
confidence: 99%
See 1 more Smart Citation
“…8 La raja es una expresión de calificación para referirse a algo extraordinario, algo muy bueno o muy divertido. 9 Bacán es en Chile la forma que se tiene para expresar algo muy bueno Education,6(3) 367 contables, asociados a la funcionalidad oral de las lenguas indígenas y a sistemas comerciales que incorporan relaciones de parentesco y de autoridades colegiadas a nivel de aldeas (Jayasinghe & Thomas, 2009) cuestiona cómo se están expandiendo formas empresariales ajenas al contexto de las comunidades a través de programas de gobierno, y sobre cómo las intervenciones que realicemos se ven influidos por campos de fuerza mayores. El marco discursivo basado en la responsabilidad individual y el emprendurismo se reafirma cuando un líder local opina que "a los indígenas nos hace falta saber ser empresarios" (R., 28/11/2012).…”
Section: Rise -International Journal Of Sociology Of Education 6(3) 345unclassified